Mobile Phone-Based Persuasive Technology for Physical Activity and Sedentary Behavior: A Systematic Review - Aldenaini, Noora; Oyebode, Oladapo; Orji, Rita; Sampalli, Srinivas (Frontiers in Computer Science, 2020)
Mobile phone technology has been progressively employed in persuasive technology interventions design to promote physical activity (PA) and discourage sedentary behavior (SB). Because of the ubiquitous nature and seamless integration of mobile phones into the user’s daily lives, mobile phone-based persuasive technologies (PTs) have the potential to influence and change a user’s behavior or attitude continuously. This paper provides a systematic review of 15 years of research (80 papers) focusing on the effectiveness of mobile phone-based PT in promoting PA and reducing SB. Specifically, this review aims to: (1) assess the effectiveness of mobile phone-based PT in persuading users to be more physically active and less sedentary, (2) highlight research trends in this area including other technology platforms implemented along with mobile phone-based PT, (3) reveal some strengths and weaknesses of existing mobile phone interventions in PA and SB domains, and (4) provide recommendations to inform future research in this area.